DAKWAH ISLAM DAN SPIRITUALITAS KEJAWEN - Chakim, Sulkhan (Fakultas Dakwah IAIN Purwokerto, 2007)
Kejawen belief teaches that the search for God must be actualized in a set of acts (laku). Laku is the way to achieve the highest level of human’s spirituality. This spirituality is present in the unity between a human being as a God’s creature and Him (manunggaling kawula Gusti). This spirituality becomes the ultimate goal of Javanese mysticism. Apart from Kejawen belief, Islam views that the highest level of human’s spirituality is iman. As a religion, Islam contains fundamental value in human life, that is godly value (iman). Iman will bear a set of values based on one God (rabbaniyah) which builds the awareness that the beginning and the end of life is from God. God is sangkan paran (the beginning and the end) of every creature’s life. Facing the changing society, da ’wa activist should be able to drive social engineering comprehensively by applying amar makruf (emancipation), nahi munkar (freedom) and tukminu billah (theological humanism).